OPTIMALISASI PENDISTRIBUSIAN BARANG DI PT.SINAR NIAGA SEJAHTERA PALU MENGGUNAKAN METODE GOAL PROGRAMMING - Hidaen, B; Jaya, A I; Resnawati, Resnawati (Program Studi Matematika, Universitas Tadulako, 2018)
PT.Sinar Niaga Sejahtera isone ofdistributorin Palu who distribute products to a variety of shops. Goal Programming is a method that can solve the problem with more than one purposes. The purposes of this study are to maximize the number of the car and minimize the distribution cost of PT.Sinar Niaga Sejahtera. Goal Programming model formulationin this research consistsof 6 priorities and 6 function constraints. The sixth priorities are,warehous capacity, the number of cars used to the distribution of goods to store Sinar Kasih II,store Cahaya Indah, store Bintang Rezeki, store Hi. Abdullah, and a minimum distribution costs. Constraint functions consist of a number of cars and the cost of distribution. The research results showed that the supply of goods by the warehouse capacity that can fulfiil the necessary distribution of goods during the month amounted to 136.93 or 8.628 box Optimal volume distribution of goods in each store are sequentially Sinar Kasih II which is 2 units with a capacity of 4 or 252 box, Cahaya Indah 3 units with a capacity of 7 or 441 box, Hi. Abdullah 2 units with a capacity of 12 or 756 box and Star 2 cars Rezeki capacity of 4 . This model can save the distribution costs of Rp. 7.127.147 from the previous distribution costs of Rp. 35.000.000.